Associations between Financial Avoidance, Emotional Distress, and Relationship Conflict Frequency in Emerging Adults in College - Josh R Novak; Rhees R Johnson (Journal of Financial Therapy, 2017)
Some research shows that college students are not aware of their financial situation and even avoid engaging with their finances. Research has yet to investigate how this financial avoidance is associated with emotional and relational health for college students in romantic relationships. As such, the purpose of this study was to identify the associations between financial avoidance and conflict frequency. Emotional distress was included as a possible mediator of the association. Results revealed that for both men and women, higher financial avoidance was indirectly associated with increased conflict frequency with their partner through increased emotional distress. A direct association was found for men. These results are important as they may give insight into increased mental health issues and relational distress in college students. Implications for practice are discussed.
Keywords: Financial Avoidance; Couple Conflict; Emotional Distress; College Students